PROJECT-BASED MATHEMATICS LEARNING: FRUIT SALAD RECIPES IN JUNIOR HIGH SCHOOL - Poppy Trianti Rahayu; Ratu Ilma Indra Putri (Journal on Mathematics Education, 2021)
Mathematics learning is associated with 21st-century skills such as communication, collaboration, critical thinking in problem-solving, creativity, and innovation. To help students obtain these skills, a learning project was developed through Pendidikan Matematika Realistik Indonesia (PMRI) approach by using fruit salad recipes and collaborative learning based on the Lesson Study for Learning Community (LSLC) system. The primary purpose of this study was to develop fruit salad recipes to assist junior high school students in solving problems using mean, social arithmetic, and data presentation. It employed design research type validation studies using photos, fruit salad products, and document reviews as data collection techniques. The research subjects were 27 students of grade 8 from a junior high school in Palembang. This study resulted in a learning trajectory consisting of two activities and post-test questions. In the first activity, the students can analyze and solve problems in planning fruit salad recipes with material averaging, social arithmetic, and data presentation. In the second activity, the students can make fruit salads and write recipes based on skills to make fruit salad products. The results of this study demonstrate that in project-based learning through PMRI with the context of fruit salad recipes and the LSLC system, students can learn collaboratively. The learning helps them solve problems by using average material, social arithmetic, and data presentation in developing fruit salad recipes.